Réponses

2014-09-08T21:37:00+02:00
A) 3/4 + 2/5
= 3 x 5 / 4 x 5 + 2 x 4 / 5 x 4
= 15/20 + 8/20
= 23/20

b) 7/3 - 2/7
= 7 x 7 / 3 x 7 - 2 x 3 / 7 x 3
= 49/21 - 6/21
= 43/21

c) - 2/5 + 1/3
= - 2 x 3 / 5 x 3 + 1 x 5 / 3 x 5
= - 6/15 + 5/15
= - 1/15

d) 5/4 + -7/6
= 5 x 6 / 4 x 6 - 7 x 4 / 6 x 4
= 30/24 - 28/24
= 2/24
= 2 x 1 / 2 x 12
= 1/12

e) 4/-9 - 5/6
= - 4/9 - 5/6
= - 4 x 2 / 9 x 2 - 5 x 3 / 6 x 3
= - 8/18 - 15/18
= - 23/18

a) 1 + 1/5
= 1 x 5 / 1 x 5 + 1/5
= 5/5 + 1/5
= 6/5

b) 2/3 - 1 = 2/3 - 1 x 3 / 1 x 3
= 2/3 - 3/3
= - 1/3

c) - 3/4 - 3
= - 3/4 - 3 x 4 / 1 x 4
= - 3/4  - 12/4
= - 15/4

d) 3 + 7/8
= 3 x 8 / 1 x 8 + 7/8
= 24/8 + 7/8
= 31/8

e) - 3/4 - 3
= - 3/4 - 3 x 4 / 1 x 4
= - 3/4 - 12/4
= - 15/4

f) - 6 - 2/7
= - 6 x 7 / 1 x 7 - 2/7
= - 42/7 - 2/7
= - 44/7